Textielactie in de Twente Hallen. Links: Van Wingerden, 2de van rechts: Engels. Kopie van origineel in bezit J. Engels
Textielactie in de Twente Hallen. Links: Van Wingerden, 2de van rechts: Engels. Kopie van origineel in bezit J. Engels.